Burden of scabies and bacterial skin infection in Kiribati: results of a national population-based survey 2023Research in context - Rebecca F. Anderson; Temea Bauro; Susanna J. Lake; Marou Tikataake; Matthew Parnaby; Jeremy Hill; Tanebu J. Tong-Kaunibwe; Anneke C. Grobler; Revite Kirition; Andrew C. Steer (The Lancet Regional Health. Western Pacific, 2025)
Summary: Background: Scabies is a treatable neglected tropical disease with a high burden in Pacific island countries. Scabies is strongly associated with bacterial skin infection, which can lead to long-term sequelae. There is a paucity of epidemiologic data from Kiribati relating to scabies and bacterial skin infection. Methods: We conducted a community-based cross-sectional survey over three weeks in November 2023 to determine the national prevalence of scabies and bacterial skin infection. Participants were recruited from ten evaluation units across all five divisions of Kiribati, including several outer islands from different island groups. All residents of visited households were eligible to participate. Trained nurses conducted clinical assessments, including focused clinical history and skin examination, for scabies and/or bacterial skin infection. Diagnosis of scabies was based on the 2020 International Alliance for the Control of Scabies diagnostic criteria. Assessment of 10,515 participants was completed. We calculated weighted prevalence, risk ratio (RR), and risk difference (RD), with 95% confidence intervals (CI), for scabies and bacterial skin infection, accounting for clustering by household. Findings: The overall weighted prevalence of scabies was 24.9% (95% CI 22.3–27.8). The highest prevalence was observed among infants aged less than 1 year at 47.2% (95% CI 40.8–53.7). Scabies was classified as moderate to severe in 64.9% (95% CI 59.1–70.2) of cases. The overall prevalence of bacterial skin infection was 7.9% (95% CI 6.8–9.2). The population attributable fraction of bacterial skin infection associated with scabies was 79.5% (95% CI 76.4–82.6). Interpretation: Our findings highlight the high burden of scabies and bacterial skin infection in Kiribati and the need for public health action to reduce the impact of both conditions. Funding: The study was funded by the Cameron Foundation (Australia) and the World Scabies Program, Murdoch Children's Research Institute.